Usborne Philosophy for beginners - Radford, Nick (Beginners series, 2020)
Philosophy is a way of thinking about just about anything. It asks big questions from nature of reality to what beauty is. Using lively examples and thought experiments, this book provides an accessible introduction to a wide range of philosophical questions and invites the reader think about things in ways they may not have done before. Cartoons, comic strips and diagrams offer simple explanations of big ideas. Suitable for adults and children alike - a brilliant resource for anyone looking to learn about philosophy. Explores big questions in philosophy including the nature of morality, do we have free will, whether knowledge is really possible and how we can justify government.